2016
DOI: 10.1071/cp15097
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction and controlled traffic considerations in Australian cotton-farming systems

Abstract: A literature review was conducted to collate best practice techniques for soil compaction management within cotton-farming systems in Australia. Universally negative effects of traffic-induced soil compaction on the whole-farm system and the wider environment include: (i) increased gap between attainable and potential yields, (ii) increased costs of energy and labour, (iii) reduced fertiliser-use efficiency, (iv) reduced water use efficiency (irrigation and rainfall), (v) increased tillage intensity. Knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 230 publications
2
29
0
2
Order By: Relevance
“…Some of the most common soil constraints in this region are high levels of salinity, sodicity, alkalinity, and compaction [1], particularly in the subsoil, but still within the rooting zone of crops. Soil salinity [2,3], sodicity [4,5], and compaction [6,7], and their impact on crops in these regions have received much attention however, there has been little emphasis on soil alkalinity constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most common soil constraints in this region are high levels of salinity, sodicity, alkalinity, and compaction [1], particularly in the subsoil, but still within the rooting zone of crops. Soil salinity [2,3], sodicity [4,5], and compaction [6,7], and their impact on crops in these regions have received much attention however, there has been little emphasis on soil alkalinity constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Such a low speed induces a longer contact between the wheel and the ground. As a consequence, the normal stress distribution is greater in the soil samples than it would have been in the field [41], but the frictional stress is lower.…”
Section: Soil Degradation By Traffic Simulationmentioning
confidence: 81%
“…The results reported in this study agree with earlier work (Kingwell and Fuchsbichler, 2011;Chamen et al, 2015) and therefore are supportive of further adoption of CTF in Europe. While quantifying the potential environmental benefits associated with CTF was not the task of this study, it is expected that improved resource use efficiency, including fertilizer, water, and energy, as well as increased soil protection will enhance the overall environmental performance compared with random field traffic (Li et al, 2007;Masters et al, 2013;Gasso et al, 2013;Chyba et al, 2014;Antille et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that CTF has fundamental advantages in maintaining soil structural conditions, with lower inputs of energy (reduced draft) and improved trafficability and timeliness, compared to conventional traffic systems (Chamen and Longstaff, 1995;Tullberg, 2000;McPhee et al, 2015). In Australia, CTF represents a profitable technological innovation for arable land use (Kingwell and Fuchsbichler, 2011), which has additional, and significant, agronomic and environmental benefits (Gasso et al, 2013), including reduced potential for greenhouse gas emissions (GHG) and enhanced fertilizer use efficiency (Torbert and Reeves, 1995;Vermeulen and Mosquera, 2009;Antille et al, 2015Antille et al, , 2016. Similar observations have been reported in reviews Chamen et al, 2015) and experimental studies conducted in Northern and Western Europe .…”
mentioning
confidence: 99%